Tan Sri Professor Emeritus Dr. Mohd. Kamal Hassan - Zeki, Akram M; Hassan, Nur Jannah (OFIIR-CENTRIS, 2024)
Professor Emeritus Dr. Mohd. Kamal Hassan (Allāh yarḥ amuhu) was a highly distinguished academic and erudite Islamic scholar of the 21st century. One of his most significant contributions was the conceptualization of the International Islamic University Malaysia (IIUM), beginning with the concept paper written by him in 1982 as assigned by the Prime Minister of Malaysia, Dr. Mahathir Mohamed, a year before the establishment of the University. His visionary concept paper laid the groundwork for the university, establishing a legacy of Ṣadaqah Jāriyah, an ongoing charity that continues to benefit generations through the academic endeavours of IIUM with continuous teaching and learning, and the abundance of various projects, research, publications, and initiatives within the University as well as reaching out to the communities, local and international.